Operasi Kemanusiaan TNI Angkatan Laut, Korps Marinir, dan Relawan Kemanusiaan dalam Penanganan Banjir Bandang di Kecamatan Langkahan, Aceh Utara - Albert Albert; Roseline Roseline; Marcell Jose Susanto; Veronica Gozali; Natasya Tjoa; Oedia Ruth Vania; Caroline Lawrencia; Kevin Kevin; Marcelluis Mendy Halim; Jovelyn Tionardi; Tasya Sanusi (Pusat Riset dan Inovasi Nasional, 2026)
Flash floods are one of the most frequent hydrometeorological disasters in Indonesia and cause significant impacts on community life, particularly in areas with high rainfall and river-dominated geographical conditions. Langkahan District, North Aceh Regency, was one of the areas severely affected by flash floods, resulting in infrastructure damage, disruption of socio-economic activities, limited access to transportation, and increased public health risks. These conditions required a rapid, coordinated, and multi-stakeholder response. As part of Military Operations Other Than War (MOOTW), the Indonesian Navy conducted a humanitarian operation involving the Marine Corps, the Marine Health Corps, and community volunteers. This operation aimed to provide evacuation assistance, emergency health services, psychosocial support, and logistical aid distribution to flood-affected communities in Langkahan District. This study employed a descriptive qualitative approach using a case study method. Data were collected through participatory observation during the humanitarian operation, semi-structured interviews with Indonesian Navy personnel, Marine Corps members, medical teams, volunteers, and affected residents, as well as documentation review. Field operations included deployment to the affected area using Marine Corps tactical trucks due to damaged road access, evacuation of residents, medical services, distribution of basic necessities, and referral of patients requiring advanced medical treatment. The results indicate that collaboration between the Indonesian Navy, Marine Corps, Marine Health Corps, and volunteers significantly improved the effectiveness of emergency response, accelerated aid distribution, and supported early community recovery. The active involvement of volunteers strengthened community trust and enhanced coordination between state institutions and local communities in disaster management.